The cingulum: anatomy, connectivity and what goes beyond - Kollenburg, L; Arnts, H; Green, A; Strauss, I; Vinke, S; Kurt, E (Oxford University Press, 2025)
For over half a century, the cingulum has been the subject of neuroanatomical and therapeutic investigations owing to its wide range of functions and involvement in various neurological and psychiatric diseases. Recent clinical studies investigating neurosurgical techniques targeting the cingulum, like deep brain stimulation of the anterior cingulate cortex and cingulotomy, have further boosted interests in this central ‘hub’ as a target for chronic intractable pain. Proper targeting within the cingulum is essential to achieve sufficient pain relief. Despite the cingulum being the centre of research for over a century, its structural and functional organization remains a subject to debate, consequently complicating neurosurgical targeting of this area. This study aims to review anatomical and connectivity data of the cingulum from a clinical perspective in order to improve understanding of its role in pain. For the current study, a systematic literature search was performed to assess the anatomy and functional and structural connectivity of the cingulate bundle and cortex. These outcomes focus on MRI and PET data. Articles were searched within the PubMed database, and additional articles were found manually through reviews or references cited within the articles. After exclusion, 70 articles remained included in this analysis, with 50, 29 and 10 studies describing human, monkey and rat subjects, respectively. Outcomes of this analysis show the presence of various anatomical models, each describing other subdivisions within the cingulum. Moreover, connectivity data suggest that the cingulate bundle consists of three distinct fibre projections, including the thalamocortical, cingulate gyrus and anterior frontal and posterior parietal projections. Further, the cingulum is responsible for a variety of functions involved in chronic pain, like sensory processing, memory, spatial functioning, reward, cognition, emotion, visceromotor and endocrine control. Based on the current outcomes, it can be concluded that the cingulum is a central ‘hub’ for pain processing, because it is a melting pot for memory, cognition and affect that are involved in the complex phenomenon of pain experience, memory, spatial functioning, reward, cognition, emotion, visceromotor and endocrine control. Variability in anatomical and connectivity models complicate proper and standardized neurosurgical targeting, consequently leading to clinicians often being reluctant on stimulation and/or lesioning of the cingulum. Hence, future research should be dedicated to the standardization of these models, to allow for optimal targeting and management of patients with chronic intractable pain.